Influência da dor na capacidade funcional de idosos institucionalizados - Reis, Luciana Araújo dos (2008)
The aim of this study was to evaluate the pain influence regarding location, intensity and duration over functional capacity in institutionalized elderly (Fundacao Leur Brito). This is a descriptive exploratory study with a transversal design and quantitative approach. The population of the study was composed of 60 elderly, being 50% males with 60 years-old minimum age and 104 years-old maximum age, with mean age 77,6 (?}11,64) years-old. Data was collected by a structured query formulary divided in four parts: 1) Social, health and demographic characterization; 2) Pain related aspects (time and location); 3) Pain evaluation by numeric scale and 4) Functional capacity measured by Barthel Index. It was observed after evaluation by Squared-chi test (x2) statistical significant difference between pain presence and Barthel Index activities: bath (pvalue=0,015), dressing (p-value= 0,041), intimal hygiene transference (p-value=0,001), chair and bed transference (p-value=0,032), walking (p-value=0,010) and go upstairs (p-value=0,008). It was also observed statistical difference between total Barthel score (dependent/independent) and pain presence, p-value<0, 000. Through data obtained by this study, a multiprofessional approach is necessary to proper pain control and maintenance and/or regain of functional capacity, leading to an increase in life quality with more independence and autonomy to elderly